Enhancement of Neurogenesis and Memory by a Neurotrophic Peptide in Mild to Moderate Traumatic Brain Injury. Issue 2 (February 2015) - Chohan, Muhammad Omar; Bragina, Olga; Kazim, Syed Faraz; Statom, Gloria; Baazaoui, Narjes; Bragin, Denis; Iqbal, Khalid; Nemoto, Edwin; Yonas, Howard
Abstract : BACKGROUND: Traumatic brain injury (TBI) is a risk factor for Alzheimer disease (AD), a neurocognitive disorder with similar cellular abnormalities. We recently discovered a small molecule (Peptide 6) corresponding to an active region of human ciliary neurotrophic factor, with neurogenic and neurotrophic properties in mouse models of AD and Down syndrome. OBJECTIVE: To describe hippocampal abnormalities in a mouse model of mild to moderate TBI and their reversal by Peptide 6. METHODS: TBI was induced in adult C57Bl6 mice using controlled cortical impact with 1.5 mm of cortical penetration. The animals were treated with 50 nmol/d of Peptide 6 or saline solution for 30 days. Dentate gyrus neurogenesis, dendritic and synaptic density, and AD biomarkers were quantitatively analyzed, and behavioral tests were performed. RESULTS: Ipsilateral neuronal loss in CA1 and the parietal cortex and increase in Alzheimer-type hyperphosphorylated tau and A-β were seen in TBI mice. Compared with saline solution, Peptide 6 treatment increased the number of newborn neurons, but not uncommitted progenitor cells, in dentate gyrus by 80%. Peptide 6 treatment also reversed TBI-induced dendritic and synaptic density loss while increasing activity in tri-synaptic hippocampal circuitry, ultimately leading to improvement in memory recall on behavioral testing. CONCLUSION: Long-term treatment with Peptide 6 enhances the pool of newborn neurons in the dentate gyrus, prevents neuronal loss in CA1 and parietal cortex, preserves the dendritic and synaptic architecture in the hippocampus, and improves performance on a hippocampus-dependent memory task in TBI mice. These findings necessitate further inquiry into the therapeutic potential of small molecules based on neurotrophic factors. ABBREVIATIONS: AD, Alzheimer disease BrdU, bromodeoxyuridine BrdU-IR, bromodeoxyuridine immunoreactive BrdU-NeuN-IR, BrdU-NeuN immunoreactive cells CCI, controlled cortical impact CNTF, ciliary neurotrophic factor DG, dentate gyrus GCL, granular cell layer LIF, leukemia inhibitory factor MAP2, microtubule-associated protein 2 MWM, Morris water maze SEM, standard error of the mean TBI, traumatic brain injury Abstract : Supplemental Digital Content is Available in the Text.